Hopping the Pond: The Normalization of North Atlantic Civil Aviation from its Origins to the Rise of the Jumbo Jet, 1919-1970 - Nicklin, Sean (Université d'Ottawa / University of Ottawa, 2016)
Flight across the North Atlantic is a routine process now, with thousands of flights carrying millions of passengers between Europe and North America every year quickly, safely, and affordably. By some measures it remains the busiest international flight corridor in the world and the most profitable for airlines. Yet there were no planes capable of making the flight a mere century ago. Aviation underwent a period of rapid development and expansion during the twentieth century that transformed the North Atlantic from a barrier into a central corridor in the global air network. This dissertation examines the development of civil aviation on the North Atlantic from 1919 to 1970, focusing on political, economic, and technological factors. Transatlantic flight was a focus of aviation but the earliest planes lacked the range needed to make the crossing. Technological improvements let pioneering aviators cross the ocean by 1919, proving that it was possible though difficult without further advances. Infrastructure also needed to be further developed since the North Atlantic was a hostile environment, with bad weather and limited facilities for aircraft in emergencies. Until 1945, the governments of the North Atlantic region thoroughly explored, studied, and built the infrastructure to make regular transatlantic possible. Postwar, governments supported their airlines through further infrastructural improvements, subsidies, by funding aeronautics, and by complex negotiations with foreign countries to open the skies to passenger travel. By 1970, transatlantic flight was a routine endeavour enjoyed by the masses and supported by systems invisible to the average traveler.
Keywords: civil aviation; commercial flight; North Atlantic; transatlantic; aircraft; infrastructure; history of technology; history of flight